Radiofrequency Ablation for Lung Carcinomas: A Retrospective Review of a High-Risk Patient Population at a Community Hospital - Nathan A. Cornish; Sarah Kantharia; Martin Oselkin; Leah Portnow; Jay Shah; Igor Brichkov; Jason Shaw; Loren Harris; Peter Homel; Debkumar Sarkar; David Mobley; Shaun Honig; et al. (The Arab Journal of Interventional Radiology)
Purpose: The purpose of this study is to retrospectively evaluate the technical efficacy, safety, and treatment outcomes of percutaneous radiofrequency ablation (RFA) of lung tumors in patients not amenable to surgery at an urban community hospital. Materials and Methods: Informed consent and IRB approval was obtained. Eligible tumors were defined as those in patients deemed poor surgical candidates by multidisciplinary consensus or those refusing surgery. Response to treatment was assessed by computed tomography (CT) performed immediately postprocedure and regular intervals up to 36 months later. Complete response was measured as a 30% decrease in mean tumor diameter without evidence of contrast enhancement or tumor growth within the ablation zone as defined by the response evaluation in solid tumors. Patient demographics, technical success, postprocedure complications, and survival were assessed and compared with data available in literature. Results: Twenty-four patients with a total of 29 tumors underwent percutaneous CT guided RFA for biopsy-proven lung malignancies between 2010 and 2016. Complete response was achieved in 82% (14/17) of treated tumors in patients who complied with postprocedure imaging recommendations. Immediate postprocedure complications occurred following 27.6% (8/29) ablations with pneumothorax being the most common, 17.2% (6/29). Mean survival is 28.5 months (95% confidence interval: 19.7–37.3). Progressive disease was seen in 18% (3/17) patients. No immediate treatment mortality was found. No significant difference was found in survival in patients with multiple comorbidities as measured by the Charlson Comorbidity Index. Conclusions: RFA of lung tumors is a well-tolerated procedure with low incidence of minor complications, a good tumor response and survival benefit in selected patients in the community setting. This is a positive endorsement of the potential success of tumor RFA programs outside of the academic setting. In addition, patients with multiple comorbidities should still be considered candidates for RFA as no difference was seen in survival in patients with multiple medical comorbidities.